O uso de pair programming em times com deficientes auditivos - Menezes, Álvaro (2021)
Studies on diversity and inclusion in Software Engineering (SE) are important to understand the differences and opportunities that there are in relation to software development teams. In teams that use agile methods, everyone involved in the project works together in a self-organized and highly collaborative way, through different practices. eXtreme Programming was developed to promote recognized good practices and encourages working in pairs. During Pair Programming programmers should communicate about possible approaches and discuss the adequacies during development with both of them reviewing each other’s contributions. For people with Hearing Disabilities this can be a barrier and a challenge to be overcome, due to difficulties in communication with hearing people. In this context, this work proposes to explore the aspects that involve diversity and inclusion in the SE scope, aiming to understand the difficulties and barriers for the inclusion of people with hearing impairment in the software development process using Pair Programming. For this, a systematic review of the literature was carried out and an online questionnaire on the subject was made available to people who practiced Pair Programming where one of the pairs was hearing impaired, in order to deepen the understanding of how this practice is used in the industry. For this study it was planned to use Grounded Theory techniques for data analysis, using an exploratory field study, using questionnaires with open and closed questions. From the data collected it was possible to conclude that good communication has a positive impact and, possibly, removing barriers and difficulties that occur on a daily basis during pairing. The results presented, suggest that good communication between peers emerges as a central theme, so that the pairing is conducted fluidly and the difficulties are restricted to tasks and their adversities.